دراسة معجمية و فوائدها في تعليم اللغة العربية - بخاري, بخاري; ياسمر, رانتي; بحر الدين, أوريل (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
Lexicographic study is an important research area in Arabic language teaching, focusing on the analysis of words and vocabulary. Researchers in this field deal with Arabic language vocabulary and its roots, which aids in a better understanding of Arabic linguistic structure. Lexicographic study serves as a valuable tool in Arabic language instruction and enhancement, offering significant benefits to learners. In this context, this research aims to highlight the importance of lexicographic study and its advantages in teaching the Arabic language. The research explores lexicographic study methods and tools and how they can be applied in educational processes. Furthermore, the research discusses how Arabic dictionaries and vocabularies can be utilized as effective teaching aids. It is important to note that lexicographic study enhances language comprehension, expands individuals' vocabularies, and improves their linguistic skills. Thus, lexicographic study plays a crucial role in strengthening the teaching and development of the Arabic language, contributing to cross-cultural and linguistic understanding among Arabic speakers. الدراسة المعجمية هي مجال بحث مهم في تعليم اللغة العربية، حيث تركز على دراسة اللغة من خلال تحليل الكلمات والمفردات. يتعامل الباحثون في هذا المجال مع مفردات اللغة العربية وتأصيلها، مما يساعد في فهم أفضل للبنية والتركيب اللغوي للعربية. تعتبر الدراسة المعجمية أداة قيمة في تعليم اللغة العربية وتحسينها، حيث يمكن للمتعلمين استفادة كبيرة منها. في هذا السياق، يسعى هذا البحث إلى تسليط الضوء على أهمية الدراسة المعجمية وفوائدها في تعليم اللغة العربية. يتناول البحث أساليب وأدوات الدراسة المعجمية وكيف يمكن تطبيقها في العمليات التعليمية. كما يبحث البحث أيضًا في كيفية استخدام المعاجم والقواميس العربية كوسائل تعليمية فعالة. تجدر الإشارة إلى أن الدراسة المعجمية تعزز فهم اللغة وتوسع مفردات الأفراد وتعزز مهاراتهم اللغوية. وبذلك، يمكن القول أن الدراسة المعجمية تلعب دورًا مهمًا في تعزيز تعليم اللغة العربية وتطويرها، مما يساهم في تعزيز التفاهم اللغوي والثقافي بين الأفراد الناطقين باللغة العربية.